Community-based education in Benin: a socio-anthropological appraisal of the social players’ perception of state - Tama, Bignon T. Clarisse (International research journal of management, IT and social sciences, 2020)
Many strategies are adopted by various stakeholders to promote education in the world as a whole, and in Benin in particular. This research work revisits the traditional conception of state-oriented and local management of international reforms proposed in order to resolve crisis situations in Africa in general and Benin in particular. This work focuses on the implementation of "partnership" in the sector of education. One of the guidelines of the 1990 Jomtien Conference has highlighted the dynamics surrounding this partnership and its implications for the perceptions that social actors’ develop about the state. The methodological approach adopted is the classic socio-anthropological one, which is intended to be as close as possible to the experiences of social actors. This is concretely based on interviews and empirical observations. The findings reveal that, while the call for partnerships has gone through the process of bringing under state control through the mobilization of different types of actors and resources for promoting a pro-mass education, it has also contributed to deconstructing the traditional conception of the state and building social actors’ perceptions about it.